pVHL-mediated SMAD3 degradation suppresses TGF-β signaling - Zhou, Jun; Dabiri, Yasamin; Gama-Brambila, Rodrigo A.; Ghafoory, Shahrouz; Altinbay, Mukaddes; Mehrabi, Arianeb; Golriz, Mohammad; Blagojevic, Biljana; Reuter, Stefanie; Han, Kang; Seidel, Anna; Đikić, Ivan; et al. (The journal of cell biology, 2021)
Transforming growth factor β (TGF-β) signaling plays a fundamental role in metazoan development and tissue homeostasis. However, the molecular mechanisms concerning the ubiquitin-related dynamic regulation of TGF-β signaling are not thoroughly understood. Using a combination of proteomics and an siRNA screen, we identify pVHL as an E3 ligase for SMAD3 ubiquitination. We show that pVHL directly interacts with conserved lysine and proline residues in the MH2 domain of SMAD3, triggering degradation. As a result, the level of pVHL expression negatively correlates with the expression and activity of SMAD3 in cells, Drosophila wing, and patient tissues. In Drosophila, loss of pVHL leads to the up-regulation of TGF-β targets visible in a downward wing blade phenotype, which is rescued by inhibition of SMAD activity. Drosophila pVHL expression exhibited ectopic veinlets and reduced wing growth in a similar manner as upon loss of TGF-β/SMAD signaling. Thus, our study demonstrates a conserved role of pVHL in the regulation of TGF-β/SMAD3 signaling in human cells and Drosophila wing development.